Bardet-Biedl syndrome: a molecular and phenotypic study of 18 families. Issue 2 (February 1997) - Beales, P L; Warner, A M; Hitman, G A; Thakker, R; Flinter, F A
Abstract : The autosomal recessive disorder Bardet-Biedl syndrome is characterised by retinal degeneration, polydactyly, obesity, mental retardation, hypogenitalism, renal dysplasia, and short stature. It is heterogeneous with at least four gene loci (BBS1-4) having been mapped to date. We have studied 18 multiply affected families noting the presence of both major and minor manifestations. Using a fluorescently based PCR technique, we genotyped each family member and assigned linkage to one of the four loci. Given this degree of heterogeneity we hoped to find phenotypic differences between linkage categories. We found 44% of families linked to 11q13 (BBS1) and 17% linked to 16q21 (BBS2). Only one family was linked to 15q22 (BBS4) and none to 3p12. We conclude that BBS1 is the major locus among white Bardet-Biedl patients and that BBS3 is extremely rare. Only subtle phenotypic differences were observed, the most striking of which was a finding of taller affected offspring compared with their parents in the BBS1 category. Affected subjects in the BBS2 and 4 groups were significantly shorter than their parents. Twenty eight percent of pedigrees did not show linkage to any known locus, evidence for at least a fifth gene. We conclude that the different genes responsible for Bardet-Biedl syndrome may influence growth characteristics such as height.